Multidisciplinary Team Meeting Proposal and Final Therapeutic Choice in Early Breast Cancer: Is There an Agreement? - Bortot, Lucia; Targato, Giada; Noto, Claudia; Giavarra, Marco; Palmero, Lorenza; Zara, Diego; Bertoli, Elisa; Dri, Arianna; Andreetta, Claudia; Pascoletti, Gaetano; Poletto, Elena; Russo, Stefania; et al. (Frontiers in Oncology, 2022)
Background A multidisciplinary team meeting (MDM) approach in breast cancer (BC) management is a standard of care. One of the roles of MDMs is to identify the best diagnostic and therapeutic strategies for patients (pts) with new diagnosis of early BC. The purpose of this study was to define whether there was an agreement between the planned program (i.e., MDMs-based decision) and that actually applied. In addition, the study explored factors associated with discordance. Methods We conducted a retrospective study of a consecutive series of 291 patients with new diagnosis of early BC, discussed at MDMs at the University Hospital of Udine (Italy), from January 2017 to June 2018. The association between clinico-biological factors and discordance between what was decided during the MDMs and what was consequently applied by the oncologist was explored through uni- and multivariate logistic regression analyses. Results The median age was 62 years (range 27–88 years). Among invasive early BC patients, the most frequent phenotype was luminal A (38%), followed by luminal B (33%), HER2-positive (12%), and triple-negative (5%). In situ carcinoma (DCIS) represented 12% of cases. The median time from MDM discussion to first oncologic examination was 2 weeks. The rate of discordance between MDM-based decision and final choice, during a face-to-face consultation with the oncologist, was 15.8% (46/291). The most frequent reason for changing the MDM-based program was clinical decision (87%). Follow-up was preferred to the chemotherapy (CT) proposed within the MDMs in 15% of cases, and to the endocrine therapy (ET) in 39% of cases (among these, 44.5% had a diagnosis of DCIS). Therapeutic change from sequential CT-ET to ET alone was chosen in 16/46 pts (35%): among these patients, seven had a luminal B disease and six had an HER2-positive disease. On univariate analysis, factors associated with discordance were values of Ki-67 14%–30% (OR 3.91; 95% CI 1.19–12.9), age >70 years (OR 2.44, 95% CI 1.28–4.63), housewife/retired status (OR 2.35, 95% CI 1.14–4.85), polypharmacy (OR 1.95; 95% CI 1.02–3.72), postmenopausal status (OR 4.15; 95% CI 1.58–10.9), and high Charlson Comorbidity Index (OR 1.31; 95% CI 1.09–1.57). The association with marital status, educational level, alcohol and smoke habits, presence of a caregiver, parity, grading, histotype and phenotype, and stage was not statistically significant. On multivariate analysis, only Ki-67 value maintained its statistical significance. Conclusion The results of our study could be useful for enhancing the role of MDMs in the clinical decision-making process in early BC.